Developing Consumer Adoption Model on Mobile Wallet in Canada - Zarrin Kafsh, Sanaz (Université d'Ottawa / University of Ottawa, 2015)
The widespread use of smartphones and technological advances in near-field communication technologies are quickly transforming mobile payment systems. These technologies have made it possible for consumers to use their smartphones to pay for their purchases through various payments systems such as Apple’s iPay, MasterPass and V.me. These mobile payment systems, commonly referred to as mobile wallets, are designed to eliminate the need for consumers to carry multiple credit cards in their wallets, thereby making it more convenient for consumers to shop. Mobile wallets represent a major advance in mobile marketing because they are another major channel through which marketers can better reach and serve customers in a very personalized way. Realizing the potential benefits of mobile wallets for both marketers and consumers depends on the speed of adoption of this new technology. This study examines the factors that influence consumers’ decision to adopt mobile wallets. Drawing on the theoretical technology adoption and diffusion literatures, a model of the factors that influence mobile wallet adoption is proposed and tested with data collected from 530 respondents. The purpose of this study was to develop a new technology acceptance model by combining TAM with IDT and exploring the factors that affect people’s behavioral intentions to use Mobile Wallet. Based on our proposed model, we explored the relationships among three innovative characteristics with PU and PEU with subjective norm which affect individuals’ intention for using Mobile Wallet. The results of this study show that some factors significantly influenced people behavioral intention to use Mobile Wallet. The effect of the trialability on the perceived usefulness is supported in this study. Subjective norm and awareness are correlated with the users’ perceived ease of use in Mobile Wallet. The findings suggest extended model of TAM for the acceptance of the Mobile Wallet can help industry players who are looking to build public demand and increase usage of Mobile Wallet.
Keywords: Mobile Wallet; Digital Wallet; TAM; Adoption